2013
DOI: 10.1002/pro.2240
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin mutations in acute myeloid leukemia: A tale of protein unfolding and mislocalization

Abstract: Nucleophosmin (NPM1) is an abundant, ubiquitously expressed protein mainly localized at nucleoli but continuously shuttling between nucleus and cytoplasm. NPM1 plays a role in several cellular functions, including ribosome biogenesis and export, centrosome duplication, chromatin remodeling, DNA repair, and response to stress stimuli. Much of the interest in this protein arises from its relevance in human malignancies. NPM1 is frequently overexpressed in solid tumors and is the target of several chromosomal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 82 publications
0
96
0
Order By: Relevance
“…Mutations in the NPM1 gene are particularly common among myeloid cancers, and are the single most common genetic cause of acute myeloid leukemia. Particularly frequent among these are mutations in the NPM1 NLSs, which cause aberrant cytoplasmic accumulation of NPM1 (termed NPM1c+) and associated DNA repair factors, marking NPM1 as a key tumor suppressor in myeloid lineages (Federici and Falini 2013). Conversely, other studies have found NPM1 overexpression to be a common feature of solid tumors from numerous different tissues, demonstrating that NPM1 can act as either a tumor suppressor or an oncogene depending on the cell and/or tissue type affected (Colombo et al 2011).…”
Section: Nucleoplasmic Translocation: a Mechanism Of Recruitment Or mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the NPM1 gene are particularly common among myeloid cancers, and are the single most common genetic cause of acute myeloid leukemia. Particularly frequent among these are mutations in the NPM1 NLSs, which cause aberrant cytoplasmic accumulation of NPM1 (termed NPM1c+) and associated DNA repair factors, marking NPM1 as a key tumor suppressor in myeloid lineages (Federici and Falini 2013). Conversely, other studies have found NPM1 overexpression to be a common feature of solid tumors from numerous different tissues, demonstrating that NPM1 can act as either a tumor suppressor or an oncogene depending on the cell and/or tissue type affected (Colombo et al 2011).…”
Section: Nucleoplasmic Translocation: a Mechanism Of Recruitment Or mentioning
confidence: 99%
“…uS3) has been reported to act as an apurinic/apyrimidinic endonuclease in both nuclear and mitochondrial base excision repair (Kim et al 2013), while nucleostemin/GNL3 has been implicated in the recruitment of RAD51 to stalled replication forks Meng et al 2013), and Nol12 has D r a f t 5 been identified as an important protective factor against oxidative DNA damage (Scott et al 2016). Most strikingly, two proteins -nucleophosmin (NPM1) and nucleolin (NCL) -are required for optimal activity of multiple independent DNA repair pathways, and their dysregulation has been reported in numerous cancers, in particular leukemias and other myeloproliferative disorders (Berger et al 2015;Colombo et al 2011;Federici et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…RAS can be supported in lattices independent of Galectin 3 by proteins such as Nucleophosmin (NPM) and Nucleolin so there are alternative non-Galectin 3 mechanisms for supporting RAS signaling(97). NPM is one of the most frequently mutated genes in AML (~35%) and this mutation results in the formation of a NES that allows the protein to be exported from the nucleus(98)(99)(100)(101)(102)(103). NPM mutations are actually associated with better survival outcome so while mutant NPM can drive leukemogenesis (perhaps via support of LSC) the mutation does not provide a survival advantage to the cancer cell(99,100).…”
mentioning
confidence: 99%
“…The mutated protein loses its ability to bind nucleoli (16) and is stably and aberrantly exported in the cytoplasm (10,11). Moreover, mutations are always heterozygous in acute myeloid leukemia patients, and mutated NPM1 oligomerizes with the wild-type protein, which is also largely translocated in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NPM1 has been shown to participate in cell cycle control, centrosome duplication, DNA repair, and responses to a variety of stress stimuli (7,8). The basis for such promiscuous behavior resides in the modular nature of the protein, which is composed of different functional domains (9,10). Among these, the C-terminal domain is responsible for nucleic acid binding and is the target of several mutations associated to acute myeloid leukemia (11).…”
Section: Nucleophosmin (Also Named B23 and Npm1mentioning
confidence: 99%